Solid–liquid Separation of Activated Sludge by Flotation Using Microporous Ceramic Diffuser - Hong, S. W.; Park, C.; Chung, T. H.; Choi, Y. S. (Journal of Applied Membrane Science & Technology, 2017)
Dissolved air flotation (DAF) is the most widely used to separate particles from liquid. However, the main disadvantage of DAF systems is the increased operating cost due to the energy requirements for the high pressure water recycling and air compressing. In this study, alumina–based porous ceramic diffusers which can produce microbubbles at low pressure regions have been developed in order to separate and thicken activated sludge solids. No bubble was generated at lower pressure (< 0.2 bar), whereas too large bubbles were generated at higher than 2.0 bar. At 1.8 bar, more than 70% of the bubbles had a diameter ranged from 20 to 60 μm. According the experimental results, the separation and thickening efficiency was mainly dependant on solid loading rate (SLR) and air to solid (A/S) ratio. When the sludge with a concentration of exceeding 5,000 mg/L was continuously fed into the flotation tank, the thickened concentration was measured to be higher than 20,000 mg/L, while SS concentrations in the clarified effluent were ranged from 5 to 10 mg/L. The experimental results revealed that the use of microporous ceramic diffusers could provide an economical, easy and reliable means of separating suspended solids (e.g., biological flocs) from liquid.